Enhanced Gravitropism of Roots with a Disrupted Cap Actin Cytoskeleton - Hou, Guichuan (American Society of Plant Biologists, 2003)
The actin cytoskeleton has been proposed to be a major player in plant gravitropism. However, understanding the role of actin in this process is far from complete. To address this problem, we conducted an analysis of the effect of Latrunculin B (Lat B), a potent actin-disrupting drug, on root gravitropism using various parameters that included detailed curvature kinetics, estimation of gravitropic sensitivity, and monitoring of curvature development after extended clinorotation. Lat B treatment resulted in a promotion of root curvature after a 90° reorientation in three plant species tested. More significantly, the sensitivity of maize (Zea mays) roots to gravity was enhanced after actin disruption, as determined from a comparison of presentation time of Lat B-treated versus untreated roots. A short 10-min gravistimulus followed by extended rotation on a 1-rpm clinostat resulted in extensive gravitropic responses, manifested as curvature that often exceeded 90°. Application of Lat B to the cap or elongation zone of maize roots resulted in the disruption of the actin cytoskeleton, which was confined to the area of localized Lat B application. Only roots with Lat B applied to the cap displayed the strong curvature responses after extended clinorotation. Our study demonstrates that disrupting the actin cytoskeleton in the cap leads to the persistence of a signal established by a previous gravistimulus. Therefore, actin could function in root gravitropism by providing a mechanism to regulate the proliferation of a gravitropic signal originating from the cap to allow the root to attain its correct orientation or set point angle.